1999
DOI: 10.1055/s-2006-960443
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA:Cholesterol Acyltransferase Inhibitory Activity of Lignans Isolated fromSchizandra, Machilus and MagnoliaSpecies

Abstract: Fifteen lignans were isolated from the fruits of SCHIZANDRA CHINENSIS, the leaves of MACHILUS THUNBERGII, and the flower buds of MAGNOLIA DENUDATA. They were identified as gomisins, schizandrin, wuweizisu, schizantherin, licarins, and machilin, which inhibited rat liver ACAT with IC (50) values of 25-200 microM. Comisin N is the most potent inhibitor with IC (50) value of 25 microM in these lignans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…were shown to reverse significantly scopolamine-induced cognitive impairments (passive avoidance response and spatial memory) in rodents. Moreover, in in vitro studies, gomisin A, C, D and G, and schizandrol B entirely inhibited acetylcholinesterase activity in dose dependent manners with IC 50 values of 6.71 ± 0.53, 6.55 ± 0.31, 7.84 ± 0.62, 12.57 ± 1.07 and 13.28 ± 1.68 M, respectively (Kwon et al, 1999;Kim et al, 2006;Hung et al, 2007). These results suggest that Schizandra lignans may be useful in the treatment of cognitive impairment, and that the beneficial effects of the drug are mediated, in part, by enhancement of the cholinergic nervous system.…”
Section: Effect On the Central Nervous Systemmentioning
confidence: 89%
See 1 more Smart Citation
“…were shown to reverse significantly scopolamine-induced cognitive impairments (passive avoidance response and spatial memory) in rodents. Moreover, in in vitro studies, gomisin A, C, D and G, and schizandrol B entirely inhibited acetylcholinesterase activity in dose dependent manners with IC 50 values of 6.71 ± 0.53, 6.55 ± 0.31, 7.84 ± 0.62, 12.57 ± 1.07 and 13.28 ± 1.68 M, respectively (Kwon et al, 1999;Kim et al, 2006;Hung et al, 2007). These results suggest that Schizandra lignans may be useful in the treatment of cognitive impairment, and that the beneficial effects of the drug are mediated, in part, by enhancement of the cholinergic nervous system.…”
Section: Effect On the Central Nervous Systemmentioning
confidence: 89%
“…Stress-protective effect: decreases damaging effects of various harmful conditions, including antioxidant, neuroprotective, hapatoprotective, cardioprotective, and gastro-protective activities; prevention of cholesterol-and methyl thiouracil-induced atherosclerosis Amitina and Vodianova (1958); Barnaulov and Shanin (1991); ; Chiu and Ko (2004); Egashira et al (2008); Fruentov and Lupandin (1976); Hung et al (2007); Ip et al (1995Ip et al ( , 1996; Ivanov et al (1958); Kim et al (2004Kim et al ( , 2006; Konstantinov (1955); Kuznetsova (1958); Kwon et al (1999); Lapajev (1967aLapajev ( ,b, 1978; Lebedev (1967); Lebedev and Kamilov (1966); Lee et al (2007); Li et al (1996Li et al ( , 1997; Liu et al (1992); Liu and Lesca (1982a,b); Liu (1991, 1992); Lupandin (1965Lupandin ( , 1967a; Lupandin and Fruentov (1968); Lupandin and Lapajev (1981); Lupandin (1965Lupandin ( , 1989a; ; Lupandin and Lapajev (1981); Ovsyanikova (1970) Stimulation of CNS Kuznetsova (1958); Lazarev (1946); Lebedev (1951a,b); Lupandin and Lapajev (1981); Pozdnyakov (1945); Sorokhtin and Minut-Sorokhtina (1958); Voevodina et al (1952); …”
Section: Effects Of Schizandra Referencesmentioning
confidence: 99%
“…In this paper, three butanolides are reported from Machilus thunbergii (Lauraceae) as new inhibitors of NO production in LPS-activated macrophages. Several kinds of biological activities of lignans from M. thunbergii have been reported, such as hepatoprotective activities as potent antioxidants (Yu et al, 2000), antibacterial activity of magnolol and honokiol (Jung and Bae, 1996) and inhibitory activity of acetylCoA:cholesterol acetyltransferase of gomisin N (Kwon et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The dried flower buds of M. biondii have historically been used for the symptomatic management of allergic rhinitis, sinusitis, and headache in Chinese medicine. 4) Previous phytochemical investigations of this species revealed that it is a valuable natural source of essential oils, 5) lignans, 6,7) neolignans, 6) sesquiterpenes, 8) flavonoids, 9) and alkaloids, 10) which have biological activities such as anti-platelet-activating factor (anti-PAF), 11) anti-inflammatory, 12) anti-allergenic, 9) and anti-angiogenic activities, 13) cholesterol acyltransferase (ACA T) inhibitory activity, 14) proapoptotic activity, 15) and vasorelaxant effects. 16) In recent research, lignans from M. biondii were demonstrated to possess anti-allergenic activity in vitro.…”
mentioning
confidence: 99%